1918-1973: действительные члены, члены корреспонденты, почетные члены, иностранные члены - Левшин Б. В. (1999)
Экземпляры: КХ (19991116) / Инвентарный номер: 1033530 / Цена: 30.00 / Сис.шифр: 72.4(2) / Авт.знак: Р 76 / ГРНТИ: 12 / ББК: 72.471.1(2Рос)